Uzbekistan boosts government support to farmers’ varieties for agro-ecology and better soil management - CGIAR Research Program on Water, Land and Ecosystems (2020)
Resolution of the Ministries of Uzbekistan #504 of 24 August 2020 ”Measures on restoration of local varieties of crops with unique traits and development of their foundation seed supply system”.